1994
DOI: 10.1128/mcb.14.5.3085
|View full text |Cite
|
Sign up to set email alerts
|

A novel mechanism of Ha-ras oncogene action: regulation of fibronectin mRNA levels by a nuclear posttranscriptional event.

Abstract: Although loss of cell surface fibronectin (FN) is a hallmark of many oncogenically transformed cells, the mechanisms responsible for this phenomenon remain poorly understood. The present study utilized the nontumorigenic human osteosarcoma cell line TE-85 to investigate the effects of induced Ha-ras oncogene expression on FN biosynthesis. TE-85 cells were stably transfected with metallothionein-Ha-ras fusion genes, and the effects of metal-induced ras expression on FN biosynthesis were determined. Induction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Interestingly, one report suggested that p38 activity in fibroblasts is negatively regulated by the presence of surface-associated fibrillar FN (Bourdoulous et al, 1998). We entertained this possibility in spite of the fact that in a majority of published reports oncogenic transformation was shown to be linked to a reduced cell surface FN level (Chandler et al, 1994;Gu and Oliver 1995;Akamatsu et al, 1996;Werbajh et al, 1998). We postulated that, in epithelial tumor cells, uPAR-dependent activation of ␣5␤1 will lead to assembly of FN fibrils, which will block p38 MAPK activity and inhibit this growth-arresting pathway.…”
Section: Introductionmentioning
confidence: 47%
“…Interestingly, one report suggested that p38 activity in fibroblasts is negatively regulated by the presence of surface-associated fibrillar FN (Bourdoulous et al, 1998). We entertained this possibility in spite of the fact that in a majority of published reports oncogenic transformation was shown to be linked to a reduced cell surface FN level (Chandler et al, 1994;Gu and Oliver 1995;Akamatsu et al, 1996;Werbajh et al, 1998). We postulated that, in epithelial tumor cells, uPAR-dependent activation of ␣5␤1 will lead to assembly of FN fibrils, which will block p38 MAPK activity and inhibit this growth-arresting pathway.…”
Section: Introductionmentioning
confidence: 47%
“…The observed decrease in transcription activity observed in FN-CAT transfections accounts for the 40-fold reduction in steady state levels of FN mRNA, leaving little room for posttranscriptional mechanisms as those caused by Ha-Ras in human osteosarcoma cells [31].…”
Section: Discussionmentioning
confidence: 97%
“…3D). The effects of Ras on mRNA stability have been documented for other mRNA molecules, such as vascular endothelial growth factor, fibronectin, nuclear factor 1, and ornithine decarboxylase (43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%